2013
DOI: 10.3389/fendo.2013.00138
|View full text |Cite|
|
Sign up to set email alerts
|

Protein Kinase C Phosphorylates the System N Glutamine Transporter SN1 (Slc38a3) and Regulates Its Membrane Trafficking and Degradation

Abstract: The system N transporter SN1 (also known as SNAT3) is enriched on perisynaptic astroglial cell membranes. SN1 mediates electroneutral and bidirectional glutamine transport, and regulates the intracellular as well as the extracellular concentrations of glutamine. We hypothesize that SN1 participates in the glutamate/γ-aminobutyric acid (GABA)-glutamine cycle and regulates the amount of glutamine supplied to the neurons for replenishment of the neurotransmitter pools of glutamate and GABA. We also hypothesize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 72 publications
(101 reference statements)
2
17
0
Order By: Relevance
“…In contrast to fibroblasts and leukocytes, levels of NAD + did not increase upon supplementation of glutamine or nicotinamide to the culture medium. As there are families of glutamine transporters with differential age-and cell-specific localization (Boulland et al 2003;Nissen-Meyer and Chaudhry 2013) these data suggest that PBSCs may lack proper glutamine transporters at this stage (as they are immature and undifferentiated) and thus exogenous glutamine may not contribute to stimulation of NAD + synthesis. Similarly, transport of nicotinamide into PBSC may have been hampered due to lack of the necessary transport systems.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to fibroblasts and leukocytes, levels of NAD + did not increase upon supplementation of glutamine or nicotinamide to the culture medium. As there are families of glutamine transporters with differential age-and cell-specific localization (Boulland et al 2003;Nissen-Meyer and Chaudhry 2013) these data suggest that PBSCs may lack proper glutamine transporters at this stage (as they are immature and undifferentiated) and thus exogenous glutamine may not contribute to stimulation of NAD + synthesis. Similarly, transport of nicotinamide into PBSC may have been hampered due to lack of the necessary transport systems.…”
Section: Discussionmentioning
confidence: 98%
“…For that reason it should be considered that these transporters may be subject to post translational regulation, a mechanism that has been broadly described for SN1 (Karinch et al, 2002;Nissen-Meyer and Chaudhry, 2013). Accordingly, different studies observed that SN1 is directly phosphorylated by the enzymes PKCα, PKCγ, and PKCδ (Nissen-Meyer et al, 2011;Sidoryk-Wegrzynowicz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of glutamine transfer between neurons and astrocytes, the small neutral amino acid transporters play an important role in the communication between these cells and thus, they are fundamental for the maintenance of the glutamate/GABA-glutamine cycle (Nissen-Meyer and Chaudhry, 2013). The SN1 and SN2 isoforms, also known as SNAT3 and SNAT5, are electroneutral transporters functioning as a Na + -glutamine symporter and H + anti-porter related to glutamine efflux from astrocytes (Chaudhry et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gamma-aminobutyric acid (GABA), the inhibitory neurotransmitter that regulates neuronal excitability, is also synthesized through the glutamine-glutamate cycle. GABA synthesis and function is beyond the scope of this review, but see [100,98,101] for review of GABA and the glutamine-glutamate cycle.…”
Section: Glutamate Release and Uptake In The Non-pathological Brainmentioning
confidence: 99%